Rasio-Rasio Keuangan dalam Memprediksi Kecurangan - Pribadi, Alfian Ronggo (Universitas Multimedia Nusantara, 2018)
The purpose of this research is to prove whether companies that commit accounting fraud with those who do not commit accounting fraud have significantly different ratio values using two accounting fraud detection models namely Beneish M-Score and Altman Z-Score. This study uses eight variables, namely debt to equity ratio, debt to total asset ratio, net profit to revenue ratio, current asset to total asset ratio, receivable to revenue ratio, inventory to total asset ratio, working capital to total asset ratio and revenue to total asset ratio. The population of this study is a manufacturing company listed on the Indonesia Stock Exchange period 2010-2016. The total sample in this research is 57 companies with the number of observations as much as 212. Hypothesis testing by using different test of independent sample t-test and logistic regression. The results of this study indicate that the variable debt to equity ratio, debt to total asset ratio, net profit to revenue ratio, working capital to total asset ratio and revenue to total asset ratio has a significant difference between companies that do accounting fraud with those who do not cheat accounting. As for the variable asset to total asset ratio, receivable to revenue ratio, and inventory to total asset ratio does not have a significant difference between companies that fraudulent accounting with those who do not commit accounting fraud.